PENGARUH DUE PROFESSIONAL CARE DAN AKUNTABILITAS TERHADAP KUALITAS AUDIT - Hadi Budiman; Yusnaini Yusnaini; Relasari Relasari (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2017)
This study was aimed at finding out the effect of due professional care and accountability to audit quality result by auditor specifically in Palembang.The population in this study are entire auditors who registered in public accountant offices specifically in Palembang totally 43 auditor. Sample study is determined with total sampling method, that mean all of 43 auditor become sample. The data resource on this study are primary data. The collecting data method was using questionnaires that distributed to all public accountant offices at Palembang. The data analysis technique used was multiple regression spesifcally due professional care and accountability as independent variable, audit quality as dependent variable.The results showed that due professional care and accountability influenced audit quality partially. This research is concluding that due professional care and accountability influence audit quality simultaneous.